Sunflower seed hulls waste as a novel source of insecticidal product: Pyrolysis bio-oil bioactivity on insect pests of stored grains and products. (10th March 2021) - Urrutia, Rodrigo Iñaki; Yeguerman, Cristhian; Jesser, Emiliano; Gutierrez, Victoria Soledad; Volpe, Maria Alicia; Werdin González, Jorge Omar
Abstract: The edible oil industry produces abundant sunflower seed hulls (SSH) as waste. Pyrolysis offers a sustainable method for producing high-value bioproducts from this lignocellulosic residue. This paper reports on the bioefficacy of SHH pyrolysis bio-oils from raw SSH (named SSH bio-oil) and acid pretreated hulls (named PTH bio-oil) as bioinsecticides against Sitophilus oryzae, Lasioderma serricorne and Tribolium castaneum . Raw SSH and pretreated hulls with 10% H3 PO4 were subjected to fast pyrolysis in a vertical reactor at 450 °C. Results show that PTH bio-oil is a furfural enriched bio-liquid with storage stability and a yield of 33%. SSH bio-oil was unsuitable for evaluating biological activity since it produce high variability in mortality data. In contrast, PTH bio-oil produces high insecticidal activity in S. oryzae (LC50  = 0.51 mg cm −2 ) by contact toxicity bioassay, followed by L. serricorne and T. castaneum . In behavioral assays, PTH bio-oil shows a slight repellent effect and mobility reduction. Moreover, PTH bio-oil affects the nutritional physiology of S. oryzae and T. castaneum producing a modification of nutritional indices and antifeedant effects. Our study provides information on the potential of fast pyrolysis bio-oils from SSH waste to develop novel bioinsecticides as an alternative to the use of conventional synthetic pesticides. Graphical abstract: Image 1 Highlights: Pyrolysis of acid pretreated SSH produces furfural-enriched bio-oil. PTH bio-oil generates lethal effects on insect pests of stored grains and products. Bio-oil affects the behavioral activity and nutritional physiology of these pests. PTH bio-oil can be used as a source of bioinsecticidal products.